HUBUNGAN KECEPATAN LARI 30 METER DAN KELENTUKAN DENGAN KEMAMPUAN LOMPAT JAUH PADA SISWA EKSTRAKURIKULER ATLETIK SMP NEGERI 2 RAMBAH - Deswanti, Seven; Putra, Muarif Arhas; Janiarli, Masdi (Journal Of Sport Education and Training, 2020)
The reasearch based exercise long jump, which some of students extra curriculer atlentic at SMPN 2 Rambah while conduct free was not maximal while conduct tumpuan was not accurate and flexibility was not good. Design of this research is correlation. The population of this research was 15 student on extra curriculer atlentic in SMPN 2 Rambah, which technique taking sample in this research was total sampling it is mean that all of the sample was of sample.The data ananlysis used correlation product moment and double correlation. Based of result finding can conclude that there was (1) there was significant correlation between run speed thirty meter with the long jump ability at student extra curriculer atlentic in SMPN 2 Rambah, with score rcount (0.603) so rx1y>rtabel (0.603>0.514), so Ho rejected Ha accepted: (2) there was significant correlation between flexibility wiith long jump ability at students extra curriculer atlentic SMPN 2 Rambah, with rcount (0.687) so rx2y>rtabel (0.687>0.514), so Ho rejected Ha accepted. (3) there was significsnt correlation between run speed thirty meter and flexibility of long jump ability at students extracurriculer atletic SMPN 2 Rambah with rcount (0.712) so rx12y>rtabel is (0.712>0.514), so Ho rejected Ha accepted